Peningkatan Jangkauan Produk dengan Pemasaran Digital pada Usaha Jus Buah Toddoppuli - Ahsani Paramita (PT. Global Research Collaboration, 2024)
The partner for this service activity is the Toddoppuli Fruit Juice MSME in Makassar City, South Sulawesi. The problems are: (1) lack of awareness in using digital marketing facilities by partners, (2) the tendency of consumers to be more interested in digital marketing, (3) the number of beverage business sales is stagnant and even tends to decrease from day to day, and (4) it is easy to access digital marketing at low cost or even free. The external target is food and beverage MSME businesses, on Jalan Toddoppuli, Makassar City, South Sulawesi. The methods used are: tutorials, demonstrations, discussions, questions and answers, and accompanying partners. The results achieved are (1) partners have knowledge in implementing digital marketing, (2) partners can market their products on social media.